Dampak Kebijakan Learning From Home Terhadap Hasil Belajar dan Motivasi Belajar Ditinjau Dari Tingkat Stres Mahasiswa: Studi di Universitas Panca Bhakti, Pontianak, Kalimantan Barat - Muhammad Adhimawan Wijaya; Hersona Sonny; Nunung Nurhasanah; DJ Suyaman (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the effect of implementing learning from home (LFH) on stress levels, learning outcomes and student motivation, as well as analyzing constraints and describing student opinions regarding the implementation of LFH. This research was conducted at Panca Bhakti University, Pontianak, West Kalimantan with the research subjects being 33 students of the 2019 Management Study Program. This study uses a combination of quantitative and qualitative analysis methods. Data was collected by distributing questionnaires to obtain data related to the implementation of LFH, learning motivation, and stress levels. Furthermore, the measurement of learning outcomes obtained from the calculation of the value of student assignments after attending lectures in LFH is carried out. To explore obstacles and student opinions regarding LFH, interviews were conducted with selected subjects. The results showed that there was no significant effect between the application of LFH and the stress level of students on learning outcomes, while for the motivation variable it was known that there was a significant effect on the application of LFH and the stress level of students.